Diseño organizacional para la fábrica de pallets "San Carlos" del cantón Quevedo, período 2012 - 2013. - Fuentes Mera, Ana Julia (2013)
This research presents a development of an organizational design for Pallets Factory "San Carlos", and in which one begins to know each of the charges that make up the current organizational structure of the factory and the system processes develops within it. To fulfill the objectives of the research were applied methodological procedures, which were focused mainly know each of the processes involved in the production of pallets and determine the degree of importance that requires the development and implementation of a Manual Functions and procedures, managing to establish the degree of importance it has for the Company and which is able to determine and classify processes are not performing effectively. For a better understanding of research information is organized by chapters: Chapter I contain the introduction, problems, formulating, systematizing, rationale and objectives to be met in the research project. In Chapter II, the theoretical framework is developed consisting of the conceptual foundations, legal and theoretical, which is based on the research project. Chapter III presents the methodology applied research, which describes the methods and techniques used in research, types of instruments and procedures that formed the basis for data collection and ensuring the reliability and validity of information. Chapter IV presents the results of the information obtained through the use of surveys to all staff Pallet Factory "San Carlos" on how to develop manufacturing processes for Pallet and based on this analysis and make the respective interpretation thereof, failing to provide a thorough evaluation regarding the processes that are affecting the normal development of the study area. Chapter V consists of the conclusions and recommendations of the research topic. Chapter VI develops the proposal for Organizational Design Manual Pallet Factory with its own scheme. Finally Chapter VII includes bibliography and appendices of the research project.